EFFECTIVENESS OF EQUIPMENT AND COMMUNITY REPRESENTATION IN SUPPORTING THE VILLAGE HEAD TO ACCELERATE THE DEVELOPMENT OF SIRNA GALIH VILLAGE - Chairul Fatulah, Muhamad; Agustiawan, M. Nassir; Hiffni, M. (Yayasan Education and Social Center, 2025)
Village development in Indonesia, as regulated in Law No. 6 of 2014 concerning Village Affairs (Village Law), emphasizes village autonomy to improve welfare through synergy among the village head, village officials, and community representation. However, the effectiveness of village officials and community representation is often an obstacle to development acceleration, especially in agrarian villages such as Sirnagalih Village, Mandalawangi District, Pandeglang Regency, Banten Province. This study aims to analyze the effectiveness of village officials in supporting the village head, the contribution of community representation through the Village Consultative Body (BPD) and deliberations, as well as non-legal and legal inhibiting factors that hinder the implementation of legal solutions. The research employs a normative-empirical approach with a descriptive-qualitative perspective, as illustrated through the case study of Sirnagalih Villa for the period from 2020 to 2023. Primary data obtained from semi-structured interviews with 25 respondents (village heads, village apparatuses, BPD, and community), participatory observation, and secondary data from legal documents such as the Village Law, Government Regulation Number 43 of 2014, and Village Fund Report (DD). Data analysis employs legal content analysis and thematic analysis, with triangulation to enhance validity. The study's results showed that the effectiveness of village officials was considered moderate (score 6.5/10), despite the implementation of the 68% DD program; however, it was hindered by a lack of competence (only 40% were trained) and weak coordination, which violated Article 62 of the Village Law. Community representation through BPD and Village Deliberation contributed 50%, with low participation (45%) and minimal supervision (30% of admitted reports), contrary to Articles 5-61 of the Village Law. The legal inhibiting factor includes unclear local regulations, while non-legal factors include a limited budget and patron-client culture. Overall, this collaboration only accelerates the construction of 20% of the RPJMDes target, with a total realization of 65%. The study concludes that the effectiveness of village officials and community representation is not optimal in supporting the acceleration of Development, despite the agrarian potential of Sirnagalih Village. Legal suggestions include a periodical revision of village apparatus training and an inclusive quota for deliberation (50% women/youth), as well as collaboration with the Ministry of Villages for national supervision. This study contributes to strengthening good governance in the Village, in line with the 2020-2024 RPJMN.